Novas métricas holísticas para avaliação da verdura de reações de síntese em laboratório - Ribeiro,Maria Gabriela T. C. (2012)
New semi-quantitative metrics for simple evaluation of global greenness of chemical reactions used in teaching laboratories, namely, the Green Circle (GC) and Green Matrix (GM), were developed. These metrics globally consider all Twelve Principles of Green Chemistry. To illustrate their construction, the greenness of several syntheses performed in the laboratory under different sets of conditions was assessed. The tools were validated by comparing the results with another metric, the Green Star (GS), developed in our previous study. Results showed these new metrics were useful for the intended purpose, having the advantage of being simpler than the GS.